2011
DOI: 10.1002/hec.1739
|View full text |Cite
|
Sign up to set email alerts
|

Using qualitative methods for attribute development for discrete choice experiments: issues and recommendations

Abstract: Attribute generation for discrete choice experiments (DCEs) is often poorly reported, and it is unclear whether this element of research is conducted rigorously. This paper explores issues associated with developing attributes for DCEs and contrasts different qualitative approaches. The paper draws on eight studies, four developed attributes for measures, and four developed attributes for more ad hoc policy questions. Issues that have become apparent through these studies include the following: the theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
519
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 441 publications
(533 citation statements)
references
References 40 publications
3
519
0
2
Order By: Relevance
“…Although the important attributes had been established through detailed qualitative work [4,9], there was remaining uncertainty about the final design in terms of the number of response categories ('levels'). The qualitative work suggested that four response categories would be most appropriate because informants did not generally feel that having an attribute 'all of the time' was realistic in terms of what could be achieved by and for those at the end of life.…”
Section: Key Uncertainty 1: Design Of the Measurementioning
confidence: 99%
See 1 more Smart Citation
“…Although the important attributes had been established through detailed qualitative work [4,9], there was remaining uncertainty about the final design in terms of the number of response categories ('levels'). The qualitative work suggested that four response categories would be most appropriate because informants did not generally feel that having an attribute 'all of the time' was realistic in terms of what could be achieved by and for those at the end of life.…”
Section: Key Uncertainty 1: Design Of the Measurementioning
confidence: 99%
“…The importance of adequately conducting and reporting development work prior to instrument valuation has recently been highlighted [4] but similar arguments are applicable to conducting and reporting pilot studies for valuation exercises; piloting is often mentioned in just one or two sentences and is seldom described in detail, thus it is difficult to discern its impact on the final study design. In contrast, the MRC framework emphasises the importance of using pilot work to "examine key uncertainties that have been identified during development" (Craig,[3] p.981) and highlights the importance of wide dissemination [3].…”
Section: Introductionmentioning
confidence: 99%
“…Starting with an initial list of nine attributes, we reduced their number through prestudies and pre-tests, following the procedure suggested by Coast et al (2012).…”
Section: Attribute Choice and Choice Setsmentioning
confidence: 99%
“…This study represents a thorough application of cognitive interviews to support the face validity of the design of the DCE and the presentation of risk attributes, and associated trading tasks. A comparable approach was taken with neurologists, which included a literature review and structured interviews, consistent with guidelines for DCE attribute selection [24]. Our inclusion of both patients' and clinicians' perspectives represents an important addition to the emerging literature on preference-elicitation in pharmacogenetics.…”
Section: Discussionmentioning
confidence: 99%